Counterrevolution : the crusade to roll back the gains of the Civil Rights Movement - Steinberg, Stephen (Stanford University Press, 2022)
In Black Reconstruction W.E.B. Du Bois wrote, "The slave went free; stood for a brief moment in the sun; then moved back again toward slavery." His words echo across the decades as the civil rights revolution, marked by the passage of landmark civil rights laws in the '60s, has seen those gains steadily and systematically whittled away. As history testifies, revolution nearly always triggers its antithesis: counterrevolution. In this book Steinberg provides an analysis of this backlash, tracing the reverse flow of history that has led to the current national reckoning on race. Steinberg puts counterrevolution into historical and theoretical perspective, exploring the "victim-blaming" and "colorblind" discourses that emerged in the post-segregation era and undermined progress toward racial equality, and led to the gutting of affirmative action. This book reflects Steinberg's long career as a critical race scholar, culminating with his assessment of our current moment and the possibilities for political transformation